2021
DOI: 10.17159/2520-9868/i82a07
|View full text |Cite
|
Sign up to set email alerts
|

Beyond classroom walls: The role of a co-curricular English club in supporting second language learning

Abstract: Second language learners of English in South Africa and beyond face challenges in acquiring the target language. In this paper, we report on a study during which we worked with an English Language Club set up as a co-curricular activity at a South African high school. We focus on one activity of the club that took place beyond the classroom walls to help learners improve their spelling. While the activities of the club were underpinned by critical pedagogy, we interpreted the findings of the study using Krashe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Co-curricular activities significantly impact the development of students' performance which is also a wonderful outlet for freedom of speech and immensely pleasurable. Sheokarah and Pillay (2021) experienced that their observations, field notes, and reflections revealed that learners can transcend their fear of the language and increase their participation levels when they are in a relaxed learning environment that values their interests, which ultimately increases their self-confidence. When the participants of this study were asked to express their self-perception towards the role of co-curricular activities in enhancing their English-speaking performance, all of them believed that co-curricular or extracurricular activities benefit them greatly, but many of them could not participate in the cocurricular activities for various reasons.…”
Section: Co-curricular Activitiesmentioning
confidence: 99%
“…Co-curricular activities significantly impact the development of students' performance which is also a wonderful outlet for freedom of speech and immensely pleasurable. Sheokarah and Pillay (2021) experienced that their observations, field notes, and reflections revealed that learners can transcend their fear of the language and increase their participation levels when they are in a relaxed learning environment that values their interests, which ultimately increases their self-confidence. When the participants of this study were asked to express their self-perception towards the role of co-curricular activities in enhancing their English-speaking performance, all of them believed that co-curricular or extracurricular activities benefit them greatly, but many of them could not participate in the cocurricular activities for various reasons.…”
Section: Co-curricular Activitiesmentioning
confidence: 99%
“…They believe their classmates will mock them. Consequently, this situation generates fear during speaking (Candido-Ribeiro, 2013;Santos & Barcelos, 2018;Sheokarah & Pillay, 2021). However, when teachers show students the importance of making learning mistakes, they may change their perspectives and see errors as positive.…”
Section: 'I Learned From My Mistakes'mentioning
confidence: 99%